Mapping MHC-encoded susceptibility and resistance in primary sclerosing cholangitis: the role of MICA polymorphism. - Norris, S; Kondeatis, E; Collins, R; Satsangi, J; Clare, M; Chapman, R; Stephens, H; Harrison, P; Vaughan, R; Donaldson, P (2001)
BACKGROUND and AIMS: Recent studies suggest that major histocompatibility complex-encoded susceptibility to primary sclerosing cholangitis (PSC) maps to the HLA B-TNFA region on chromosome 6p21.3. METHODS: The present study uses a standard polymerase chain reaction protocol to investigate the 16 common alleles of the MICA locus as candidates in 2 patient populations (King's College Hospital, London, and John Radcliffe Hospital, Oxford). RESULTS: The MICA*002 allele was found in 4 of 62 (6.4%) patients and none of 50 patients vs. 41 of 118 (35%) controls (pc = 0.00018, odds ratio [OR] = 0.12, and P = 0.0000016, OR = 0.0, respectively). Overall, the MICA*008 allele was more common in PSC (gene frequency 66% vs. 48% of controls, P = 0.0023, OR = 2.11). However, unlike MICA*002 in which the difference was a result of the absence of MICA*002 heterozygotes, the MICA*008 association may be caused by an increased frequency of MICA*008 homozygosity in patients (58% vs. 22%, pc = 0.000015, OR = 5.01 and 58% vs. 22%, P = 0.0000056, OR = 4.51, respectively). Though MICA*008 is found on the ancestral 8.1 haplotype, stratification analysis indicates that this association is independent of B8 and other HLA haplotypes associated with PSC. CONCLUSIONS: The MICA*002 allele has a strong dominant effect in reducing the risk of PSC, whereas the increased risk of disease associated with MICA*008 may be a recessive effect requiring 2 copies of the MICA*008 allele.